1924
DOI: 10.1084/jem.39.2.275
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Peroxide in Cultures of Pneumococcus

Abstract: McLeod and Govenlock (1) in 1921 reported the occurrence in pneumococcus cultures of a heat-labile substance which was inhibitory to the further growth of this and other organisms. The name bactericidin was first suggested by these authors. Further work by McLeod and Gordon (2,3) indicates that this substance is hydrogen peroxide, and that it may occur in cultures of organisms other than pneumococcus, as Bacillus bulgaricus, Bacillus acidophilus, and certain coccal and sarcinal forms. In a recent communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1925
1925
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…Under aerobic conditions, cultures of S. pneumoniae strains are known to accumulate unusually high concentrations of H 2 O 2 , which necessitates the addition of catalase to the medium for full growth (2,19). We confirmed that S. pneumoniae strain GTC13809, a serotype 19 clinical isolate used throughout the present work, behaved as a typical wild type in this respect (Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Under aerobic conditions, cultures of S. pneumoniae strains are known to accumulate unusually high concentrations of H 2 O 2 , which necessitates the addition of catalase to the medium for full growth (2,19). We confirmed that S. pneumoniae strain GTC13809, a serotype 19 clinical isolate used throughout the present work, behaved as a typical wild type in this respect (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Under aerobiosis, however, pyruvate is also known to be converted to acetate, with acetyl phosphate being the intermediate capable of phosphorylating ADP to yield ATP by the action of acetate kinase (30). The H 2 O 2 -forming flavoprotein pyruvate oxidase (EC 1.2.3.3, the product of the spxB gene), which catalyzes the formation of acetyl phosphate, CO 2 and H 2 O 2 from pyruvate, orthophosphate, and O 2 , has been shown to be involved in this pathway and also to account for most of the H 2 O 2 produced by aerobically growing S. pneumoniae cells (23,30). Massive production of H 2 O 2 has been a well-known hallmark of this bacterium since the time of Oswald Avery (2,19), usually necessitating the addition of catalase to the culture medium to obtain full growth under aerobic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 O 2 rapidly diffuses through eukaryotic cell membranes to damage intracellular targets (e.g., mitochondria and DNA) (15,45) and to trigger apoptosis. Pneumococcus is the only meningeal pathogen that lacks catalase and therefore produces excessive amounts of H 2 O 2 (14,46). Pneumococcal-derived H 2 O 2 appears to be an additional bacterial factor contributing to increases of intracellular ROS and Ca 2+ and release of AIF.…”
Section: Discussionmentioning
confidence: 99%
“…Biological production of extracellular HOOH has been known since the 1920s, from the work of several researchers (including Oswald Avery, decades before his ground-breaking work identifying DNA as the genetic material) (McLeod and Gordon, 1922;Avery and Morgan, 1924). In the ocean, microbial cells are significant sources of net HOOH, both at the surface, where it can rival photochemically produced O 2 2 (Moffett and Zajiriou, 1990;Avery et al, 2005;Vermilyea et al, 2010;Roe et al, 2016), and below the euphotic zone (200-50001 m), where it's thought to be the dominant source of the low (1-10 nM) but detectable HOOH concentrations (Yuan and Shiller, 2004;Vermilyea et al, 2010).…”
Section: Other Species May Need Cross-protection From Hoohmentioning
confidence: 99%